Pengembangan Instrumen Sound Wave Two Tier (Sowatt) Diagnostic Test: Analisis Rasch Model - Muhhammad Fadlan; Nour Fadillah; Winny Liliawati; Ika Mustika Sari (Pendidikan Fisika Universitas Nurul Huda, 2024)
This study aims to describe the validity of a sound wave diagnostic test instrument that can be used to identify students' conceptions. The research method used was Research and Development with the 4D model. The test instrument consisting of 15 questions with a two-tier format was tested on 64 students at one of the high schools in Bandung City. The results of the content validity of the instrument by experts were analyzed using a multi-rater test, namely the Many Facet Rasch Model (MRFM). As for construct validity, it was analyzed using Rasch modeling which describes validity, reliability, differentiating power, and item difficulty. The results showed that based on item dimensionality it was declared valid and every item met the criteria for item suitability with details of 3 easy questions, 11 medium questions, and 1 difficult question. Reliability based on Cronbach's alpha value is in the very good category, item reliability value is in the very good category, and person reliability is in the good category. The instrument can discriminate between individuals who have low and high abilities as seen from the results of the differentiating power test with all items in the very good category